Effect of increasing the rate of water temperature on the softening of root vegetables in boiling water - Sato, Yoko; Fujimoto, Maho (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
In Japan, the empirical method for preventing root vegetable collapse is to place them in room temperature water and then heating them. This study aims to determine the effects of water temperature increase rate on the softening and optimum boiling duration of the Japanese radish and potato. We found that the lower the rate of increase in water temperature, the lower the softening rate constants (k) of both the radish and potato. With decreasing rates of water temperature increase, the optimum boiling duration of radish increased. However, because the potato softened easily before boiling, the difference in optimum boiling duration among all rates of water temperature increase was very small. The k and degree of methylation (DM) of pectin showed a linear relationship, which suggested that the decrease in DM is the main reason for the reduction in k at low rates of water temperature increase.